OBJECT-ORIENTED APPROACH FOR THE ASSESSMENT OF MOMENTCURVATURE RELATIONSHIP OF A VARYING-WIDHT AND MULTI-MATERIAL BEAM CROSS SECTION - Pah, Jusuf J. S. (Jurnal Teknik Sipil, 2011)
This research developed the rational approach to shear design in 1984 Canadian Code Provision into a new approach which is object-oriented in fashion, and presented it for the purpose of assessing moment-curvature-relationship of a varying-width and multimaterial beam cross section. Unlike the traditional method that views a cross section as a single entity, this new approach views a section as a composition of autonomous objects. In this approach, a cross section is recognized as a system which is made up of objects, of which each can be predicated uniquely; behave autonomously in responding to loading, and capable of communication between each other. Being in such a fashion, the approach was shown to be capable to faithfully represent a section which varies in width, and is made up of materials with different mechanical characteristics, in whatever possible arrangement. To compensate for the painstaking computation that may be involved in the approach, and maintain its object-oriented fashion, an-objectoriented computer-software that uses an object-oriented user interface platform was recommended to be provided as an auxiliary to the approach.